Did the labour market matching efficiency change in Poland i 2003-2008? - Gałecka-Burdziak, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The author addresses the problem of potential fluctuations in the matching process efficiency in Poland in the time span of 2003–2008. This period reflects a systematic upward movement along a Beveridge curve, so we can expect minor (if any) reallocation and efficiency changes. However, knowing that the trade process is time- and resource-consuming and that on average it depends on the number of agents in the labour market and other variables, the author expresses doubt if it is homogenous even along the UV curve. The author uses aggregate time series and estimates various matching functions models handling econometrically for temporal aggregation bias in the data, and employs the concept of augmented matching function. At the disaggregated level the assumption of agents homogeneity is tested and the values of several mismatch indices in occupational and regional perspectives are computed. The aggregate matching function models estimates are in line with theoretical indications and prove no changes in the efficiency of the labour market matching process. It is hard, however, to confirm the assumption of agents homogeneity. In general, the analysed time span is characterized by an increase of labour market tightness indices, a decrease of unemployment rates and, in fact, minor mismatch changes (a slight increasing tendency with negligible value changes). This set indicates a lower aggregate disequilibrium
Argumenta Oeconomica, 2017, Nr 2 (39), s. 91-110
Keywords: matching function; mismatch; data temporal aggregation